Status Ketahanan Pangan dan Faktor Sosio-Ekonomi pada Masyarakat Pesisir Kabupaten Buru Selatan - Christiana Titaley; Ninik Ma’athia Sallatalohy; Felecia Petrosina Adam (agriTECH, 2020)
Food security was one of the global issues, especially in developing countries, including Indonesia. This study aimed to examine the status of food security and its related factors in the coastal communities in the area of Buru Selatan District, Maluku Province. This study used secondary data collected from a household health survey conducted by the Faculty of Medicine, Pattimura University in November 2017. Information is derived from 899 respondents aged 20−60 years. Food security status was measured using the US Household Food Security/Hunger Survey Module (USFSSM). Factors ranging from environmental, household and individual levels are included in the analysis. Logistic regression method was applied to determine factors associated with food security status. Of the 899 respondents interviewed, only 30% was food secured and about 70% suffered fromfood insecurity (33,7% experienced food insecurity with hunger). Respondents from Waesama Sub-district were more food secured than those from Kepala Madan Sub-district (aOR = 2,16, 95% CI: 1,33-3,52, p=0,002). Respondents from "very rich" households were three and a half times more food-secured than "very poor" households (aOR = 3,49, 95% CI: 2,13-5,73, p<0,001). In addition, those who paid for the membership of health insurance were more food secured than those who got waived payment of contributions (aOR = 1,49, 95% CI: 1,07-2,08, p=0.018); and respondents living in an ideal household density (8 m2 or more per person) were more food secured than those innot ideal condition (aOR = 1,55, 95% CI: 1,01-2,39, p=0,047). Our study showed that intersectoral collaboration is important to improve community’s food security status. Long and short term interventions aimed at reducing poverty and providing subsidized foods, including fortified ones, to the those in need accompanied by educational programs to improve community knowledge about various alternative of local food are essential.